Impact of cardiovascular risk factors and disease on length of stay and mortality in patients with acute coronary syndromes. (1st October 2016) - Loudon, B.L.; Gollop, N.D.; Carter, P.R.; Uppal, H.; Chandran, S.; Potluri, R.
Abstract: Background: Traditional risk factors for cardiovascular disease (CVD) have been thoroughly investigated. We aimed to investigate the impact of comorbid cardiovascular risk factors and diseases on length of stay (LOS) and mortality in patients presenting with acute coronary syndromes (ACS). Methods: We examined prevalence of CVD, LOS and mortality from 25, 287 consecutive admissions for ACS from seven hospitals across North West England between 2000 and 2013 using the ACALM (Algorithm for Comorbidities, Associations, Length of stay and Mortality) protocol using ICD-10 and OPCS-4 coding systems. Results: Mean LOS was 7.0 days and there were 9653 (38.2%) deaths in the ACS cohort over the 13-year period. Hypertension and hyperlipidaemia were associated with decreased LOS (6.95 and 4.8 days respectively, P < 0.001) and mortality (36.8% and 19.4% respectively, P < 0.001), as was angina pectoris (5.4 days and 33.5%, P < 0.001). Type 2 diabetes was associated with increased LOS and mortality (7.8 days, P < 0.05; 44.4%, P < 0.001), whereas type 1 diabetes was associated with increased mortality only (7.0 days, P = 0.42; 41.3%, P < 0.001). Other concomitant CVD was associated with an increased LOS and mortality: peripheral vascular disease (8.6 days, P < 0.05; 53%, P < 0.001), atrial fibrillation (10.9 days, P < 0.001; 63.5%, P < 0.001), cerebrovascular disease (15.9 days, P < 0.001; 76%, P < 0.001), heart failure (11 days, P < 0.001; 69.9%, P < 0.001), and ischaemic heart disease (6.7 days, P < 0.001; 38.7%, P < 0.05). Conclusion: CVD risk factors have a significant and varied impact on LOS and mortality in patients with ACS and it may be inappropriate to group them when assessing in-hospital risk. These factors should be used to identify patients at an increased risk of prolonged admissions and death post-ACS, and services should be directed accordingly.